Motility of Amphistegina lobifera throughout the High Concentration Trial HCT experiment - Christiane Schmidt; Diana N Puerto Rueda; Moritz Nusser; Clinton A Oakley; Xavier Pochon; Marleen Stuhr; Débora Raposo; Simon K Davy (PANGAEA, 2025)
This dataset captures foraminiferal motility during the High Trial experiment. It documents the number of Amphistegina lobifera individuals attached to the culturing jar walls and tracks variations in motility over time in response to experimental treatments.
In: Schmidt, C et al. (2025): Menthol-DCMU bleaching experiments on two foraminifera species, Amphistegina lobifera and Sorites orbiculus [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974618